Suhu dan Kelembaban Nisbi, Peranannya dalam Penyimpanan Bawang Bombay - Suharwadji Sentana (agriTECH, 1999)
Onion as a perishable product cannot be stored for long periods, due to various factors. Major deterioration problems that occur during onion storage are weight loss, sprouting, root growth, diseases, sugar accumulation, loss of pyruvic acid and ascorbic acid. Combination of relative humidity and temperature could prevent or minimize onion losses during storage, however, it depends on onion cultivar. Pyruvic acid is a trademark of onions and is the main factor why this vegetable is used in food industries throughout the world. Loss of ascorbic acid indicates loss in quality or loss in other nutrients components such as carbohydrate and protein. Sprouted bulbs cannot be used anymore, except for seedlings, while rooted and rotted bulbs by removing 2.3 outer skin layer of rotted bulbs and cutting or trimming rooted bulbs, onions can still be used for cooking. Loss of weight also results in unattractive appearance. Loss of weight more than 10% causes onion wilting, or even drying. Storage temperature and relative humidity are two important factors which must be considered if this product will be stored successfully. Onions can be stored at either low (t 0°C) or high temperature (t 30°C) and at particular humidity. The ideal combination of storage temperature and relative humidity could prolong storage life of onions. In general, storage temperature of 0°C and 30°C and relative humidity of 60% - 75% are an ideal condition for storing onions. This review also outlines the ideal combination of storage temperature and humidity for particular onion cultivars.